PENGARUH LEVERAGE, UKURAN PERUSAHAAN DAN KEPEMILIKAN MANAJERIAL TERHADAP KONSERVATISME AKUNTANSI - Nurul Rizkiaeni Ganevia; Nina Karina Karim; Robith Hudaya (Jurnal Bisnis Terapan, 2022)
Abstract This research aims to determine the effect of leverage, firm size and managerial ownership on accounting conservatism of property and real estate companies that listed on the Indonesia Stock Exchange (IDX) in 2017-2019. This type of research is quantitative research. The data collection process was carried out using documentation techniques and literature studies that referred to the literature of previous studies. The sampling technique used purposive sampling method. This research uses 63 samples of property and real estate companies that listed on the Indonesia Stock Exchange (IDX) in 2017-2019 period. This research used multiple linear regression for data analysis. The results of this research indicate that leverage has no effect on accounting conservatism, while firm size and managerial ownership have a negative effect on accounting conservatism. This research has implications for the management to consider the factors that influence accounting conservatism in the financial statements, as well as to become information for investors in considering investment decisions.